Anionic uranyl oxyfluorides as a bifunctional platform for highly selective ion-exchange and photocatalytic degradation of organic dyes. Issue 42 (5th September 2018) - Yue, Zenghui; Lin, Jian; Silver, Mark A.; Han, Ling; Li, Xiaoyun; Zhou, Jing; Guo, Xiaojing; Bao, Hongliang; Huang, Yu-Ying; Wang, Jian-Qiang
Abstract : Anionic uranium oxyfluorides with tunable open-volumes were synthesized and they exhibit selective ion-exchange and photocatalytic properties toward methylene blue. Abstract : Uranium is unique owing not only to its intriguing physiochemical properties, but also to the diverse coordination chemistry that uranyl adopts and bonding that enables rich and unpredictable topologies of uranium-bearing materials. Six anionic uranium oxyfluorides with various dimensionalities, including a 3D framework (MeUF ), four 2D lamellar structures (EtUF-1, PrUF, BuUF-1, andBuUF-2 ), and a 1D chained topology (EtUF-2 ), have been rationally constructed by employing tetra-alkyl ammonium ions as structure-directing agents. By combining the tunable interlayer distance of the lamellar structures with the photooxygenation properties of uranyl ions, a bifunctional platform for highly selective ion-exchange and photocatalytic degradation over organic dyes has been developed. Specifically, BuUF-2 can efficiently capture 94.5% methylene blue (MB + ) within 24 h from solution with remarkable selectivity related to both the size and the charge of organic dyes. Such size- and charge-dependent selectivity toward organic dyes has been documented for MOFs, but is rare for 2D lamellar materials. Furthermore, the removal ofMB + can be largely accelerated under UV radiation ( e.g. 84.7% forBuUF-2 within 1 h) due to the photocatalytic activities ofEtUF-1, EtUF-2, PrUF, andBuUF-2 .